Antarctic environmental management: achievements and challenges (on the 25th anniversary of the Madrid Protocol) - A. P. Fedchuk (Ukrainian Antarctic Journal, 2016)
The 25th anniversary of the signing of the Protocol on Environment Protection to the Antarctic Treaty (the Madrid Protocol), to be celebrated in 2016, provides a great opportunity to assess the effectiveness of the implementation of its provisions within the scope of the larger issues on evolution of the Antarctic environmental management and protection, which currently is one of the priorities for the Antarctic Treaty Parties. This article critically examines the environmental legal tools adopted at the Antarctic Treaty Consultative Meetings. The main attention is paid to the analysis of the provisions and structure of the Madrid Protocol and its Annexes, as well as institutional and procedural tools developed by its executive body - the Committee for Environment Protection, CEP (such as the application of Environmental Impact Assessments, conservation of flora and fauna, avoiding pollution of the marine environment, waste management, establishing procedures for area protection and management). The current challenges related to effective Antarctic environmental protection are both human (the extension of national scientific expeditions programs, including the creation of new scientific facilities and transport infrastructure, further growth of international tourism activities) and natural challenges due to changes in the environment (climate change and reducing sea ice, the introduction of non-native biological species). Thus, the outstanding issues of the Protocol implementation are the following: providing an effective mechanism to reduce the cumulative impact of human activities on the Antarctic environment; international cooperation related to the proliferation of stations; more active practical application of the precautionary approach in planning and carrying out Antarctic activities; strengthen the environmental impact assessment process for both governmental scientific and non-governmental commercial activities; and further systematic development of the representative Antarctic protected areas network. The CEP’s multi-year strategic work plan is considered as an organizational and analytical tool focused on environmental issues that should be urgently settled on a priority basis.